2018
DOI: 10.19109/biota.v4i1.1626
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFIKASI BAKTERI PADA TUBUH LALAT RUMAH (Musca domestica Linn.) DI TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) DAN PASAR

Abstract: Several species of flies are the most important species in public health problems, especially as a disease transmission vector. One of them is Musca domestica. The role of flies in the spread of disease is as a mechanical vector, by bringing the seeds of disease through the limbs. Therefore it is necessary to understand what bacteria found in the body of M. domestica fly in Sukawinatan landfill, Palembang. This study aimed to find out the type of bacteria in the body of M. domestica in Sukawinatan landfill, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
2
1
0
4
Order By: Relevance
“…and Vibrio Cholera bacteria, but no parasites. This result was in line with the previous study by Yunita (18) , which has found the Salmonella sp, Providencia, Escherichia and Vibrio in the fly body around the Sukawintan landfill. The typhoid disease occursdue to Salmonella sp infection in the intestinal tract (18) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…and Vibrio Cholera bacteria, but no parasites. This result was in line with the previous study by Yunita (18) , which has found the Salmonella sp, Providencia, Escherichia and Vibrio in the fly body around the Sukawintan landfill. The typhoid disease occursdue to Salmonella sp infection in the intestinal tract (18) .…”
Section: Discussionsupporting
confidence: 93%
“…This result was in line with the previous study by Yunita (18) , which has found the Salmonella sp, Providencia, Escherichia and Vibrio in the fly body around the Sukawintan landfill. The typhoid disease occursdue to Salmonella sp infection in the intestinal tract (18) . Salmonella sp in the landfill's flies was suspected because of the stack of organic and inorganic trash that produced leachate, which can be a suitable medium for the microorganism such as bacteria and parasite to grow.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Penelitian yang dilakukan oleh Carneiro (2014) pada lalat di Brazilia mengidentifikasi beberapa spesies bakteri yang terdapat di lalat, yaitu: Aquaspirillum polymorphum, Burkholderia ambifaria, Burkholderia anthina, Burkholderia cepacia, Burkholderia cenocepacia, Burkholderia pyrrocinia, Burkholderia stabilis, Paenibacillus macerans, Virgibacillus pantothenticus, Bacillus subtilis. Hasil penelitian lain dilakukan oleh Putri (2018) di Pasar Jakabaring Palembang dengan hasil bahwa Lalat rumah (Musca domestica Linn) teridentifikasi sebagai vektor dari bakteri Salmonella sp dan Proteus sp. Bagian eksoskeleton Lalat Musca domestica Linn teridentifikasi bakteri Escherichia coli, dan Salmonella sp.…”
Section: Pendahuluanunclassified
“…Menurut Khamesipour et al, (2018) (Safitri, Hastutiek, & Arimbi, 2017). Hal ini kemudian dipertegas oleh hasil identifikasi bakteri di Tempat Pembuangan Akhir (TPA) sampah dan pasar yang menemukan bakteri genus Salmonella, Providencia, Escherichia dan Vibrio pada lalat yang berasal dari TPA, serta bakteri genus Salmonella dan Proteus pada lalat yang berasal dari pasar (Putri, 2018).…”
Section: Hubungan Kelembaban Dengan Kepadatan Lalatunclassified